Introductory Business Statistics - Holmes, Lex; Illowsky, Barbara; Dean, Susan (Open textbook library., 2017)
Introductory Business Statistics is designed to meet the scope and sequence requirements of the one-semester statistics course for business, economics, and related majors. Core statistical concepts and skills have been augmented with practical business examples, scenarios, and exercises. The result is a meaningful understanding of the discipline, which will serve students in their business careers and real-world experiences.